Álvaro Vieira Pinto e Heleieth Saffioti intérpretes do Brasil : pressupostos para o desenvolvimento e o feminismo em suas obras - Cipriani, Cristian (2020)
CIPRIANI, Cristian. Álvaro Vieira Pinto and Heleieth Saffioti interpreters from Brazil: assumptions for development and feminism in their works. 2020. Thesis in Education. Programa de Pós-Graduação em Educação (PPGEdu), Profa. Dra. Edla Eggert (profesor adviser) – Escola de Humanidades da Pontifícia Universidade Católica do Rio Grande do Sul. Porto Alegre – RS, 2020. Álvaro Borges Vieira Pinto (1909-1987) and Heleieth Iara Bongiovanni Saffioti (1934-2010) are characters who dedicated their lives to interpreting the Brazilian social, political, economic and educational structures. Indeed, this academic endeavour characterizes itself as a theoretical-philosophical study, essentially grounded on the philosophy of Vieira Pinto and on the sociology of Heleieth Saffioti. The research method anchors in Hans-Georg Gadamer and Martín Heidegger’s precepts of hermeneutics summed up with the counterpoint of feminist hermeneutics. From Gadamer the horizon principle remains, whereas Heidegger’s idea of hermeneutics circle is sought. From feminist hermeneutics, questions are brought to the idea of universality and tradition as factors of truth. Throughout the thesis, the method of exposure is guided by dialectics, according to the proposal made by Álvaro Vieira Pinto. Thus, when exposing understandings an argumentative construction is sought, one that starts first from the whole to the parts and then from the parts to the whole, with the objective of carrying out synthesis, whenever possible. All the works from Álvaro Vieira Pinto, as well as Heleieth Saffioti’s, were read and scrutinized. The stories and trajectories of the authors were outlined in order to justify their perspective, and then to explore the relation between their ideas and the political and ideological context of the time. The conclusion is that the analysis made about Brazil indicate, each one in its way, the exploitation-domination that usurp the full development possibilities of the national human being. These socio-political and economic structures generate deleterious effects on education, society and on the lives of the people who live here. In this sense, this thesis analyses how Álvaro Vieira Pinto and Heleieth Saffioti interpreted Brazil, as well as apprehends the educational assumptions of these interpretations to identify which categories merge in the filigree of their hermeneutic horizons. For both, the Brazilian oppressions occur due to the current socio-political and economic systems, but Saffioti, the established relationship is between patriarchy-racism-capitalism, whereas to Vieira Pinto such oppressions are based on underdevelopment-imperialism. Keywords: Álvaro Vieira Pinto. Heleieth Iara Bongiovanni Saffioti. Underdevelopment-imperialism. Patriarchy-racism-capitalism. Education.